2022
DOI: 10.1111/1755-0998.13699
|View full text |Cite
|
Sign up to set email alerts
|

High‐quality genomes reveal significant genetic divergence and cryptic speciation in the model organism Folsomia candida (collembola)

Abstract: The collembolan Folsomia candida Willem, 1902, is widely distributed throughout the world and has been frequently used as a test organism in soil ecology and ecotoxicology studies. However, it is questioned as an ideal “standard” because of differences in reproductive modes and cryptic genetic diversity between strains from various geographical origins. In this study, we obtained two high‐quality chromosome‐level genomes of F. candida, for a parthenogenetic strain (named FCDK, 219.08 Mb, 25,139 protein‐coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 180 publications
1
7
0
Order By: Relevance
“…According to previously reported genome assemblies (Faddeeva-Vakhrusheva et al, 2017; Luan et al, 2023), the architecture of the Hox cluster in F. candida exhibits genomic rearrangement, with Scr , Antp and Ubx inserted into the anterior region of the complex. This organization showed that the Hox genes lack spatial collinearity (Figure 3A) (Faddeeva-Vakhrusheva et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…According to previously reported genome assemblies (Faddeeva-Vakhrusheva et al, 2017; Luan et al, 2023), the architecture of the Hox cluster in F. candida exhibits genomic rearrangement, with Scr , Antp and Ubx inserted into the anterior region of the complex. This organization showed that the Hox genes lack spatial collinearity (Figure 3A) (Faddeeva-Vakhrusheva et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…BRAKER trained Augustus v. 3.3.4 [46] and GeneMark-ES/ET/EP 4.68_lic [47] integrating evidence from the OrthoDB10 v.1 database [48]. GeMoMa with parameters 'GeMoMa.c = 0.3 GeMoMa.p = 12 00 utilized eight species (Daphnia magna (GCF_003990815.1) [49], Cloeon dipterum (GCA_902829235.1) [50], Zootermopsis nevadensis (GCF_000696155.1) [51], Drosophila melanogaster (GCF_000001215.4) [52], Rhopalosiphum maidis (GCF_003676215.2) [53], Tribolium castaneum (GCF_ 000002335.3) [54], Sinella curviseta (https://doi.org/10.6084/m9.figshare.24635850) and FCSH (GCA_020923455.1)) [7] as the protein homology-based reference. RNA-seq alignments were produced using HISAT2 v. 2.2.0 [55].…”
Section: (B) Genome Assembly and Annotationmentioning
confidence: 99%
“…These studies use chromosome-banding techniques to provide important insights into chromosome number and size characteristics [3][4][5]. Previous research has revealed that chromosome numbers in collembolan species vary between 5 and 11, and this observation is also supported by publicly available genomic data [3][4][5][6][7][8]. Furthermore, Collembola exhibit significant variations in chromosome size among different species.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations